Effect of Different Dose of Nitrogen and Phosphorous on Gladiolus Yield at Ilam, Nepal - Basnet, M.; Shakya, S.M.; Pant, S.S. (Himalayan Biodiversity, 2017)
An experiment was conducted to assess the effect of different levels of nitrogen and phosphorus on Gladiolus yield of cultivar (cv.) Jester in Ilam municipality-2 Fulgachi, Ilam. The research was conducted at the Department farm of Bachelors of Science in Horticulture and Floriculture Management (B.Sc. HFM), Ilam from April to September 2014. The experiment consisted of twelve treatment combinations laid out in factorial randomized complete block design with three replications. Four levels of nitrogen 0 kg, 50 kg, 100 kg and 150 kg/ha were experimented as the first factor and three levels of phosphorous 0 kg, 50 kg and 100 kg/ha formed were taken as the second factor which comprised of twelve treatment combinations. Nitrogen and phosphorous significantly affected plant height, number of leaves per plant, spike length, days to first cutting, days to last cutting and yield (number of corm per plant) of Gladiolus plant.